2016
DOI: 10.1038/nmat4539
|View full text |Cite
|
Sign up to set email alerts
|

Underwater contact adhesion and microarchitecture in polyelectrolyte complexes actuated by solvent exchange

Abstract: Polyelectrolyte complexation is critical to the formation and properties of many biological and polymeric materials, and is typically initiated by aqueous mixing1 followed by fluid–fluid phase separation, such as coacervation2–5. Yet little to nothing is known about how coacervates evolve into intricate solid microarchitectures. Inspired by the chemical features of the cement proteins of the sandcastle worm, here we report a versatile and strong wet-contact microporous adhesive resulting from polyelectrolyte c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
384
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 410 publications
(389 citation statements)
references
References 30 publications
(34 reference statements)
3
384
1
1
Order By: Relevance
“…Phase inversions are common in the manufacture of polymeric membranes and typically are driven by changes in interfacial energy, viscosity and surface area between the phases (Strathmann and Kock, 1977). A recent investigation of a synthetic coacervate model system inspired by mussel adhesion revealed that complex coacervates can undergo phase inversion to form a structured fluid; the continuous inverted fluid phase then hardens to form a load-bearing porous material (Zhao et al, 2016). The relevance of these results to plaque formation remains to be demonstrated with plaque proteins.…”
Section: Protein Secretion and Fluid-fluid Phase Changesmentioning
confidence: 99%
“…Phase inversions are common in the manufacture of polymeric membranes and typically are driven by changes in interfacial energy, viscosity and surface area between the phases (Strathmann and Kock, 1977). A recent investigation of a synthetic coacervate model system inspired by mussel adhesion revealed that complex coacervates can undergo phase inversion to form a structured fluid; the continuous inverted fluid phase then hardens to form a load-bearing porous material (Zhao et al, 2016). The relevance of these results to plaque formation remains to be demonstrated with plaque proteins.…”
Section: Protein Secretion and Fluid-fluid Phase Changesmentioning
confidence: 99%
“…[29] A catechol-functionalized weak polyanion (poly-(acrylic acid)) was premixed with a polycation(bis-(trifluoromethane-sulphonyl)imide (Tf 2 N)) in dimethyl sulphoxide (DMSO). [30] Based on the influence of dielectric constants (ɛ) to ionization in weak polyelectrolytes, [31] the solvent exchange between DMSO and water can realize the robust underwater adhesion (W ad ≥2 J•m 2 ) with the electrostatic complexation, phase inversion, and rapid setting (~25 s). [30] The complexed underwater adhesive is applied to various substrates, such as plastics, glasses, metals, biological materials.…”
Section: Molecular Design Principle Of Musselinspired Polymeric Undermentioning
confidence: 99%
“…[30] Based on the influence of dielectric constants (ɛ) to ionization in weak polyelectrolytes, [31] the solvent exchange between DMSO and water can realize the robust underwater adhesion (W ad ≥2 J•m 2 ) with the electrostatic complexation, phase inversion, and rapid setting (~25 s). [30] The complexed underwater adhesive is applied to various substrates, such as plastics, glasses, metals, biological materials. [30] These biomimetic approaches may accelerate the development of the adhesives for industrial or biomedical applications.…”
Section: Molecular Design Principle Of Musselinspired Polymeric Undermentioning
confidence: 99%
See 1 more Smart Citation
“…Gecko foot encourages another kind of amazing bioinspired study from the viewpoint of surface adhesion,6 together with other natural adhesive systems like plant,7 insect,8 tree frog,9 octopus,10 and mussel 11. The most popular mechanical interlocker, velcro12 (hook‐loop interlocker) inspired by the hooks of burdock, has been applied in many fields since it was invented, such as clothing, room apparatus, and medical bandages.…”
mentioning
confidence: 99%